Representações sociais do reino animal: a sacralização do animal humano - Costa, Susana Gonçalves (Trabalhos de Antropologia e Etnologia, 2020)
The way we see and relate with de animal kingdom depends on a large range of cultural features, such as religion. While Hinduism and Buddhism have a more ecocentric view of the world, the religions that are part of the Judaism and Christianity Paradigm (i.e. Judaism, Christianity and Islamism) have a more anthropocentric approach. As such, for the latter three religions animal kingdom is divided in two opposed poles, “good” and “bad” animals. Humans are outside and above all the other living beings, adopting a domination position. This manuscript seeks to briefly “visit” the sociozoologic model of the Jewish, Christian and Islamic cultures trying to justify the origins of the human superiority concept.